Environmental perception-an experimental basic design atelier for students of architecture: An assessment - Gökan, Rıfat Koray (PION LTD, 207 BRONDESBURY PARK, LONDON NW2 5JN, ENGLAND, 2001)
An assessment is presented of the changes that have occurred in visual creative design activities of students participating in an experimental 'basic design atelier'. At the Department of Architecture, Istanbul Kültür University, such an atelier is a requirement for the first-year students. Among the factors affecting creative design activity the following are closely monitored: (a) Visual creative design activities are based upon perceived environmental phenomena. (b) These activities are also based on experience; so the priority is given to students' own yet limited experience to express selected aspects (conceptual or physical) of any environmental phenomena; 'basic design' is dependent upon masterly use of students' own vision. (c) Physical aspects of phenomena are essential to understand their formal and spatial functioning. (d) Students' total personality and preferences are inevitably involved in making aesthetic decisions; (e) Art changes dynamically in accordance with the intellectual and emotional concepts of the periods contemplated.
Keywords: Psychology; Experimental Psychology; Psikoloji; Deneysel Psikoloji